Common Heritage of Humankind: International-Legal Aspect - MAMEDOV, Andrey Alievich; MIRZAEE, Siavash; ABASHIDZE, Aslan Khuseinovich; VAKULA, Marina Anatolievna; SOLNTSEV, Alexander Mikhailovich (Journal of Advanced Research in Law and Economics, 2018)
The common heritage of humankind takes a prominent place in the law of the sea and international space law. Given the gap between the developing and developed countries in the current era, and the increasing trend of using and depleting rare resources of the earth and outer space, the necessity of using the common heritage of humankind as a rescue factor was experienced. The success of this concept in the seabed (Part XI of the United Nations Convention on the Law of the Sea) and steps taken in outer space to implement it (the 1979 Moon Treaty), inspired to use it in some new spheres that seem to be in danger. These new spheres are Human Genome, Fossil Aquifers, and Cultural Heritage. The paper used a scientific methodological approach which facilitates to identify the whole canvas of the research, identify the main aspects and concepts of the study. The research used scientific methods of cognition, i.e. analysis, dialectics and synthesis, the method of generalization and system-structural method. In this paper, the author examines other items able to be identified as the common heritage of humankind and practical use, such as Human Genome, Fossil Aquifers, and Cultural Heritage. By identifying the new proposed cases of the common heritage of humankind, it is possible to use them as an instrument to filling the gap between developing and developed countries and guarantee justice among all nations.